2018
DOI: 10.3892/ijmm.2018.3371
|View full text |Cite
|
Sign up to set email alerts
|

Genistein attenuates di‑(2‑ethylhexyl) phthalate-induced testicular injuries via activation of Nrf2/HO‑1 following prepubertal exposure

Abstract: Di-(2-ethylhexyl) phthalate (DEHP) and genistein (GEN) are of the most common endocrine disrupting chemicals (EDCs) present in the environment or the diet. However, investigation of the effects of acute exposure to these two EDCs during prepuberty has been lacking. In this study, DEHP and GEN were administrated to prepubertal male Sprague-Dawley rats by gavage from PND22 to PND35 with vehicle control, GEN 50 mg/kg body weight (bw)/day, DEHP50, 150 and 450 mg/kg bw/day, and combined treatment. Reproductive para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 58 publications
4
21
0
Order By: Relevance
“…Keap1-Nrf2 signaling is a key antioxidant system that can detoxify exogenous toxicants to maintain cellular homoeostasis 17 , 40 , 41 . Decreased Nrf2 rendered cells susceptible to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keap1-Nrf2 signaling is a key antioxidant system that can detoxify exogenous toxicants to maintain cellular homoeostasis 17 , 40 , 41 . Decreased Nrf2 rendered cells susceptible to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The role of oxidative stress in DEHP-induced IR was also emphasized in a cross-sectional pilot study in which exposure to DEHP at the community level promoted IR in 10-13-year-old children by inducing systemic oxidant stress, characterized by the increased urinary level of F2-isoprostane 15 . Nrf2 is a master regulator of the cytoprotective program against oxidative stress and, more importantly, has the capability to detoxify DEHP 16 , 17 . Our previous study indicated a critical role for the Nrf2-mediated antioxidant response in DEHP-induced rat insulinoma INS-1 cells dysfunction 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Culty et al [12] reported that fetal testosterone biosynthesis was suppressed via activation of peroxisome proliferatoractivated receptors (PPARs) after phthalate exposure; in this process, imbalance in prooxidant/antioxidant ratio was induced and reactive oxygen species (ROS) production was elevated [12]. Our previous studies revealed that exposure to MEHP at doses higher than human exposure level induced the impairment of testicular antioxidative enzyme activities, and oxidative stress aggravated testicular injuries as the doses increased [6,7]. Other studies also observed an increased apoptosis rate of spermatocytes, atrophy of testis, and high sperm DNA fragmentation index together with elevated ROS level [46,47].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…However, the combined effects after exposure to at least two kinds of EDCs have rarely been investigated [5]. Genistein (GEN), a kind of soy isoflavones commonly present in the Asian diet [6], and mono-(2-ethylhexyl) phthalate (MEHP), the metabolite of the widely used plasticizer di(2-ethylhexyl) phthalate (DEHP), are two kinds of the most prevalent EDCs which act via different mechanisms [7]. In previous studies, genistein was categorized as a weak estrogenic phytoestrogen, but more recently, it was found to be a potential antioxidant [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation